The Meaning Of “Ngidang Ngobeng” Tradition In Palembang City - Misnawati, Desy; Nursila, Nursila (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
Ngidang Ngobeng comes from the word "ngidang" which means sitting cross-legged on the floor and "ngobeng" which means attendant. Ngidang is the tradition of serving food, while Ngobeng is a special officer to assist guests in the Ngidang Ngobeng tradition. This Ngidang Ngobeng activity has become a hereditary tradition in Palembang City and is part of the culture of the Palembang people. The tradition of ngidang ngobeng has begun to fade among the community, especially in the younger generation, in Palembang City today, the tradition of ngidang ngobeng is gradually being eroded by changes in lifestyle and modernization. Palembang people who live in urban areas tend to be more practical and busy so the ngidang ngobeng tradition is less routinely carried out than it used to be. This can threaten the continuity and preservation of this valuable cultural tradition. Therefore, this research aims to find out the meaning of the ngidang ngobeng tradition in Palembang City. This research uses descriptive qualitative methods with data collection techniques of observation, interviews, and documentation. The theory used uses Phenomenological Theory. The result is that the Ngidang Ngobeng tradition has the meaning of cooperation, honoring guests, togetherness, fostering intimacy, connecting communication between communities, having an Islamic nature, and fostering a sense of social in the process of implementing the Ngidang Ngobeng tradition. Ngobeng tradition is a tradition of Palembang people in living togetherness which is often found at meal events such as weddings, akikah, and other big events.